An In-depth Analysis of Rendered Models using Blender : A Research Result - Raheem, Oluwafunmilayo; Omijeh, Bourdillon; Ibeachu, Chinagorom (JITCE (Journal of Information Technology and Computer Engineering), 2024)
The research investigated the efficiency of a novel virtual reality (VR) method for anatomy education utilizing a web application designed for virtual dissection. This platform encompasses various features, including virtual dissection, quizzes, a chat forum, and direct messaging, transforming it into a virtual dissection classroom. To evaluate the efficiency of the virtual reality system we compared the web application with other existing web applications using parameters such as Accuracy, Precision, Jaccard index, Dice co-efficient, Processing time, and user rating. From the result obtained from the research in comparing the rendered models from this research with models from other work, the rendered models were able to achieve a Jaccard index of 0.93 and a dice coefficient of 0.94. It also achieved a remarkable average processing time of 15 seconds and a high user rating of 4.5.